Tactile stimulus is essential to increase motivation for touch interaction in virtual environment. (2nd September 2021) - Higashino, Kana; Kimoto, Mitsuhiko; Iio, Takamasa; Shimohara, Katsunori; Shiomi, Masahiro
Abstract : This paper reports the effectiveness of a tactile stimulus in a virtual environment to increase people's motivations during a monotonous task by comparing a touch with only visual stimuli and another with both visual and tactile stimuli. Although touch interaction with robots showed various positive effects such as improved motivation, visual and haptic stimuli were not separated due to the form of the touch in physical environments. Virtual environments enable us to investigate such effects by separating the modality of touch: a visual-only-touch and a visual-tactile touch. We experimented in a virtual environment where participants did a monotonous task after experiencing either a visual-only-touch or a visual-tactile-touch by an agent to compare them in the context of motivation improvements and the perceived impressions. The experimental results showed that a visual-tactile touch significantly increases the motivations of the participants for monotonous tasks. On the other hand, their likability of the agents is not significantly changed by the touch modalities. GRAPHICAL ABSTRACT: UF0001